Where does the truth lie? Petty violence in the light of court records in Poland in the first half of the 18th century (Theatrum historiae, 2013)
The omnipresence of different forms of violence, perceived as one of the ways of defending own interests and resolving conflicts, was practically a fundamental element of the popular culture of the early modern time. Petty violence is understood as all forms of unacceptable assaults – verbal and physical aggression – that does not cause serious injury, but because of its burdensomeness and frequency was treated as inadmissible and the people experiencing it sued perpetrators in local courts. The social acceptance for some types of behaviour – “reasonable correction” of wives by husbands, children by parents, servants by masters or mistresses – caused that the judges regarded such complaints with reservation and required evidence and witnesses, temporizing verdicts. Contrary to the popular belief, a tendency to resolve conflicts by force was not exclusive to men, but characterised also women, weaker in terms of physical strength. However, while male violence seemed quite natural, criminal acts committed by women were perceived as some form of aberration that went against the image of women widely accepted in the Polish history. However, this is not a question of sex, but of character, social attitudes and behaviours.
Keywords: petty violence; domestic conflicts; women violence; female crimes; male violence; the popular culture; old Poland; early modern era